Improvement method for liquid outlet uniformity of slit coating mold and application of improvement method

By forming a hydrophilic coating on the surface of the slit coating mold, the problem of uneven coating film thickness is solved, the liquid output uniformity and film thickness uniformity are improved, defects and increased series resistance are reduced, and the quality of perovskite films and solar cells is improved.

CN119608529APending Publication Date: 2025-03-14RENSHUO SOLAR (CHANGSHU) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411789260.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In slit coating technology, the problem of uneven coating film thickness leads to a decrease in coating quality, reduced efficiency, and may lead to product quality problems.

Method used

By forming a hydrophilic coating on the surface of the mold coating on the slit, the wettability of the mold surface is improved, and the liquid forms a uniform thin layer on the surface, thereby stabilizing the liquid flow rate and liquid output.

Benefits of technology

The uniformity of the slit coating liquid is improved, and the thickness uniformity of the obtained coating film is reduced, defects such as holes and problems such as increasing series resistance are reduced, and the preparation capability of the perovskite film and the stability of the solar cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608529A_ABST
    Figure CN119608529A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the liquid outlet uniformity of a slit coating mold and application of the method. The improvement method comprises the following steps that the surface of the slit coating mold is coated with hydrophilic paint, a hydrophilic coating is formed on the surface of the slit coating mold, and the slit coating mold with uniform liquid outlet is obtained; the slit coating mold surface includes a lip surface of the slit coating tool bit and a receiving chamber surface. According to the method for improving the liquid outlet uniformity of the slit coating mold, the liquid outlet uniformity of slit coating can be improved, and the thickness uniformity of a prepared coating film is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slit coating, and in particular relates to a method for improving liquid discharge uniformity of a slit coating die and an application thereof. Background Art

[0002] Slit coating is a commonly used coating method. It is a coating technology that presses the coating liquid along the gap of the mold under a certain pressure and transfers it to the moving substrate. It has the characteristics of fast coating speed and wide coating window. However, in practical applications, the problem of uneven thickness of the coating film produced by slit coating is very common. The uneven thickness of the coating film will affect the coating quality, reduce the coating efficiency, and even cause product quality problems.

[0003] CN114192342A discloses a high uniformity coating head device for a slit coating device and a method for using the same. The high uniformity coating head device for a slit coating device is installed on a liftable bracket of the slit coating device, and is a first coating head device of a pump-free system consisting of a half-sheet coating head, a roller and a solution feed port, or a second coating head device with a pump system; the half-sheet coating head is composed of a first half-sheet coating head and a second half-sheet coating head, and the first half-sheet coating head and the second half-sheet coating head form a receiving chamber, and the receiving chamber contains and stores a target solution injected through the solution feed port; the roller is installed at the bottom of the half-sheet coating head, communicates with the receiving chamber, and is located above a substrate placed on the slit coating device; during operation, the coating head device is lifted and lowered by the bracket, so that the outer surface of the bottom of the roller is fully in contact with the surface of the substrate, the slit coating device drives the substrate to move horizontally, the target solution flows through the receiving chamber to the outer surface of the roller, and the target solution is continuously and evenly coated on the surface of the substrate to form a thin film by rolling the roller.

[0004] CN105170406A discloses a slit coating unit, a coating head and a coating device, wherein the slit coating unit comprises a housing, wherein a feed channel for fluid inflow, a discharge channel for fluid outflow, a pressure-dividing channel connecting the feed channel and the discharge channel, and a slit nozzle arranged at the end of the feed channel are arranged in the housing, wherein the width of the feed channel decreases step by step in a direction toward the slit nozzle. The slit coating unit provided by the technical solution can improve the problem of uneven film coating caused by unstable feed flow rate.

[0005] In order to solve the problem of uneven coating film thickness produced by slit coating, the coating film thickness uniformity is usually improved by changing the coating machine structure and optimizing the coating process parameters. However, it is difficult to change the coating machine structure and the controllability of optimizing the coating process parameters is poor.

[0006] In the coating process of perovskite, the main technical difficulty of large-area perovskite film formation is that the uniformity, thickness and flatness of the film are difficult to control during large-area film formation, and defects such as holes are prone to occur, resulting in low quality of perovskite film and increased series resistance, thereby affecting the stability of battery output.

[0007] Therefore, it is necessary to develop a method for improving the uniformity of liquid discharge from a slot coating die. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention aims to provide a method for improving the uniformity of liquid discharge from a slit coating die and its application. The method for improving the uniformity of liquid discharge from a slit coating die can improve the uniformity of liquid discharge from the slit coating die and make the thickness of the obtained coating film uniform.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for improving the uniformity of liquid discharge from a slit coating die, the preparation method comprising the following steps: coating a hydrophilic coating on the surface of the slit coating die to form a hydrophilic coating on the surface of the slit coating die to obtain a slit coating die with uniform liquid discharge;

[0011] The surface of the slit coating die includes a lip surface of the slit coating blade and a surface of the accommodating chamber.

[0012] Surface tension is the force of mutual attraction between liquid molecules, which causes a certain contact angle to appear when the liquid contacts the solid surface. The present invention improves the wettability of the surface of the slit coating die by forming a hydrophilic coating on the surface of the slit coating die, so that the liquid forms a uniform thin layer on the surface, thereby making the flow rate and liquid output from the lip of the slit coating blade more stable, thereby improving the uniformity of the slit coating liquid output and making the thickness of the obtained coating film uniform.

[0013] Preferably, the slit coating die is a slit coating die cleaned with an organic solvent or a surfactant.

[0014] In the present invention, cleaning with an organic solvent or a surfactant can effectively remove grease, dust or impurities on the surface of the slit coating die, which is helpful for subsequently forming a hydrophilic coating on the surface of the slit coating die.

[0015] Preferably, the organic solvent includes any one of acetone, anhydrous ethanol or isopropanol, or a combination of at least two of them.

[0016] Preferably, the surfactant includes any one of polyether polyol 3300IN, secondary alcohol AEO-9 or isooctyl alcohol polyoxyethylene ether, or a combination of at least two thereof.

[0017] Preferably, the hydrophilic coating is a super hydrophilic coating.

[0018] Preferably, the water contact angle of the super hydrophilic coating is ≤5°, for example, 1°, 1.5°, 2°, 2.5°, 3°, 3.5°, 4° or 4.5°, etc.

[0019] Preferably, the hydrophilic coating comprises any one of an inorganic nano-silicon coating, a nano-titanium dioxide coating or a hydrophilic polymer coating.

[0020] Preferably, the coating comprises spraying.

[0021] Preferably, the spraying amount is 8 to 15 g / m 2 , for example 9g / m 2 , 10g / m 2 , 11g / m 2 , 12g / m 2 , 13g / m 2 or 14g / m 2 etc., more preferably 8 to 10 g / m 2 .

[0022] In the present invention, the spraying amount is preferably 8 to 10 g / m 2 If the spraying amount is too much, the adhesion is poor and peeling is easy to occur. If the spraying amount is too little, the hydrophilic effect of the slit coating mold is poor and the liquid discharge uniformity is poor.

[0023] Preferably, the hydrophilic coating comprises an inorganic nano-silicon coating or a nano-titanium dioxide coating, and the step of forming the hydrophilic coating on the surface of the slit coating mold specifically comprises the steps of drying and sintering.

[0024] Preferably, the drying temperature is 60-100°C (for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, etc.), and the drying time is 10-30min (for example, 12min, 14min, 16min, 18min, 20min, 22min, 24min, 26min or 28min, etc.).

[0025] Preferably, the sintering temperature is 120-400°C (for example, 150°C, 180°C, 210°C, 240°C, 270°C, 300°C, 330°C, 360°C or 390°C, etc.), and the sintering time is 10-30 min (for example, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min or 28 min, etc.).

[0026] Preferably, the preparation method of the inorganic nano-silicon coating comprises the following steps:

[0027] (a) Mix hydrochloric acid and water to prepare a hydrochloric acid solution.

[0028] (b) mixing ethyl orthosilicate and a solvent, adding the hydrochloric acid solution obtained in step (a), stirring, and standing to obtain a SiO2 sol.

[0029] (c) mixing the SiO2 sol obtained in step (b) with a surfactant, stirring, and standing to obtain the inorganic nano-silicon coating.

[0030] Preferably, the molar ratio of water to hydrochloric acid in step (a) is 1:(0.02-0.05), for example, 1:0.025, 1:0.03, 1:0.035, 1:0.04 or 1:0.045, etc.

[0031] Preferably, the molar ratio of the tetraethyl orthosilicate to the solvent in step (b) is 1:(4-8), for example, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7 or 1:7.5, etc.

[0032] Preferably, the molar ratio of tetraethyl orthosilicate to hydrochloric acid is 1:(0.05-0.1), for example, 1:0.055, 1:0.06, 1:0.065, 1:0.07, 1:0.075, 1:0.08, 1:0.085, 1:0.09 or 1:0.095, etc.

[0033] Preferably, the solvent in step (b) comprises ethanol.

[0034] Preferably, the surfactant in step (c) comprises cetyltrimethylammonium bromide and / or sodium lauryl sulfate.

[0035] Preferably, the mass of the surfactant in step (c) is 1% to 5% of the mass of the SiO2 sol, for example, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%, etc.

[0036] Preferably, the step (b) of adding the hydrochloric acid solution prepared in step (a) is the step of dropwise adding the hydrochloric acid solution prepared in step (a).

[0037] Preferably, the stirring temperature in step (b) is 20-60°C (for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C or 55°C, etc.), and the time is 1.5-2.5h (for example, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h or 2.4h, etc.).

[0038] Preferably, the standing time in step (b) is 15 to 20 h (e.g., 15.5 h, 16 h, 16.5 h, 17 h, 17.5 h, 18 h, 18.5 h, 19 h or 19.5 h, etc.).

[0039] Preferably, the stirring temperature in step (c) is 20-40°C (for example, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C, etc.), and the time is 1.5-2.5h (for example, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h or 2.4h, etc.).

[0040] Preferably, the standing time in step (c) is 8 to 24 h (e.g., 10 h, 12 h, 14 h, 16 h, 18 h, 20 h or 22 h, etc.).

[0041] Preferably, the preparation method of the nano titanium dioxide coating comprises the following steps:

[0042] (A) Butyl titanate, acetic acid and a solvent are mixed to obtain a light yellow solution.

[0043] (B) Mixing the light yellow solution obtained in step (A) with a nitric acid solution to obtain a nano titanium dioxide coating.

[0044] Preferably, the volume ratio of butyl titanate, acetic acid and solvent in step (A) is 10:(1-3):(25-35), for example, 10:1.5:28, 10:1.5:30, 10:1.5:32, 10:2:28, 10:2:30, 10:2:32, 10:2.5:28, 10:2.5:30 or 10:2.5:32, etc.

[0045] Preferably, the mixing in step (A) is stirring mixing, the stirring temperature is 20-40°C (for example, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C, etc.), and the time is 15-60min, for example, 20min, 25min, 30min, 35min, 40min, 45min, 50min or 55min, etc.

[0046] Preferably, the nitric acid solution in step (B) comprises nitric acid, ethanol and water.

[0047] Preferably, the volume ratio of the nitric acid, ethanol and water is 0.5:(8-12):(0.5-1.5), for example, 0.5:9:0.8, 0.5:9:1, 0.5:9:1.2, 0.5:10:0.8, 0.5:10:1, 0.5:10:1.2, 0.5:11:0.8, 0.5:11:1 or 0.5:11:1.2, etc.

[0048] Preferably, the volume ratio of the light yellow solution to the nitric acid solution in step (B) is 42:(5-15), for example, 42:6, 42:7, 42:8, 42:9, 42:10, 42:11, 42:12, 42:13 or 42:14, etc.

[0049] Preferably, the mixing in step (B) is stirring mixing, the stirring temperature is 20-40°C (for example, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C, etc.), and the time is 1-2h (for example, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h or 1.9h, etc.).

[0050] Preferably, the hydrophilic coating comprises a hydrophilic polymer coating.

[0051] Preferably, the hydrophilic polymer coating comprises a hydrophilic polymer.

[0052] Preferably, the hydrophilic polymer comprises a hydroxyl-containing hydrophilic polymer or a carboxyl-containing hydrophilic polymer.

[0053] Preferably, the hydroxyl-containing hydrophilic polymer includes any one of polyethylene glycol, polyvinyl alcohol or polyvinyl pyrrolidone, or a combination of at least two thereof.

[0054] Preferably, the carboxyl-containing hydrophilic polymer comprises polyacrylic acid.

[0055] In a second aspect, the present invention provides a slit coating die with uniform liquid discharge, wherein the slit coating die with uniform liquid discharge is prepared by the method for improving the uniformity of liquid discharge of a slit coating die as described in the first aspect.

[0056] In a third aspect, the present invention provides a use of a slit coating mold with uniform liquid discharge as described in the second aspect in a coating process of perovskite.

[0057] In the present invention, by adopting the method for improving the uniformity of liquid discharge from a slit coating die as described in the first aspect, a hydrophilic coating is formed on the surface of the slit coating die, and a slit coating die with uniform liquid discharge is prepared. The perovskite film prepared by using the slit coating die has good thickness uniformity, can effectively reduce the occurrence of defects such as holes, increased series resistance, and other problems, can improve the ability to prepare large-area high-quality perovskite absorption layers, and prepare perovskite solar cells with good stability.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] The method for improving the uniformity of liquid discharge from a slit coating die of the present invention is prepared by forming a hydrophilic coating on the surface of the slit coating die, so that the flow rate and liquid discharge amount of the liquid squeezed out from the lip of the slit coating blade are more stable, the uniformity of liquid discharge from the slit coating is improved, and the thickness uniformity of the prepared coating film is good. The water contact angle of the hydrophilic coating is ≤11°, and preferably, the water contact angle of the hydrophilic coating is ≤5°. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 A schematic diagram of the water contact angle of the hydrophilic coating provided in Example 1;

[0061] Figure 2 A schematic diagram of the water contact angle of the hydrophilic coating provided in Example 2;

[0062] Figure 3 A schematic diagram of the water contact angle on the surface of the slit coating die provided for Comparative Example 1;

[0063] Figure 4 The thickness uniformity test result of the perovskite film prepared in Application Example 1;

[0064] Figure 5 The thickness uniformity test result of the perovskite film prepared in Application Example 2;

[0065] Figure 6 The thickness uniformity test results of the perovskite film prepared in comparative application example 1 are shown. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] Preparation Example 1

[0068] This preparation example provides an inorganic nano-silicon coating, which is prepared by the following method:

[0069] (a) mixing water and hydrochloric acid in a molar ratio of 1:0.022 to prepare a hydrochloric acid solution;

[0070] (b) mixing tetraethyl orthosilicate and anhydrous ethanol in a molar ratio of 1:6.4, slowly dropping the hydrochloric acid solution prepared in step (a), wherein the molar ratio of tetraethyl orthosilicate to hydrochloric acid is 1:0.085, stirring at a constant temperature of 40° C. for 2 h, and standing for 18 h to obtain a SiO2 sol;

[0071] (c) adding cetyltrimethylammonium bromide to the SiO2 sol prepared in step (b), wherein the mass of cetyltrimethylammonium bromide is 3% of the mass of the SiO2 sol, stirring at a constant temperature of 25°C for 2 hours, and standing for 24 hours to obtain an inorganic nano-silicon coating.

[0072] Preparation Example 2

[0073] This preparation example provides a nano titanium dioxide coating, specifically nano titanium dioxide coating A, which is prepared by the following method:

[0074] (A) Add 30 ml of anhydrous ethanol to a reaction flask, stir vigorously, add 10 ml of butyl titanate and 2 ml of acetic acid at once, stir for 20 min, and obtain a uniform, transparent, light yellow solution;

[0075] (B) Under vigorous stirring at 500 rpm, a nitric acid solution (composed of 0.5 ml of nitric acid, 10 ml of anhydrous ethanol and 1 ml of water) was added dropwise to the light yellow solution obtained in step (A), and stirring was continued at 25° C. for 1 h to obtain a nano-titanium dioxide coating A.

[0076] Preparation Example 3

[0077] This preparation example provides a nano titanium dioxide coating, specifically a nano titanium dioxide coating B, which is prepared by the following method:

[0078] (A) Add 30 ml of anhydrous ethanol to a reaction flask, stir vigorously, add 10 ml of butyl titanate and 3 ml of acetic acid at once, stir for 60 min, and obtain a uniform, transparent, light yellow solution;

[0079] (B) Under vigorous stirring at 500 rpm, a nitric acid solution (composed of 0.5 ml of nitric acid, 10 ml of anhydrous ethanol and 1.5 ml of water) was added dropwise to the light yellow solution obtained in step (A), and stirring was continued at 25° C. for 2 h to obtain a nano-titanium dioxide coating B.

[0080] Preparation Example 4

[0081] This preparation example provides a hydrophilic polymer coating, which is prepared by the following method: 100 ml of water is added to a reaction bottle, 10 g of polyacrylic acid (weight average molecular weight is 2000) is added, and the mixture is heated and stirred at 40° C. until it is completely dissolved, and then 10 g of an acrylic resin adhesion promoter (Condilon SE6628) and 1 g of a crosslinking agent isocyanate (Trixene BI7963 from Lanxess Chemical, HDI biuret) are added. ) , and stirring is continued for 1 hour to obtain the hydrophilic polymer coating.

[0082] Example 1

[0083] The present embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge, the improvement method comprising the following steps: cleaning the lip surface and the receiving chamber surface of the slit coating blade in the slit coating die with polyether polyol 3300IN, and then spraying the inorganic nano-silicon coating provided in Preparation Example 1 on the lip surface and the receiving chamber surface of the slit coating blade, with a spraying amount of 10 g / m 2 , drying at 100°C for 10 minutes, and high-temperature sintering at 300°C for 10 minutes to form a hydrophilic coating on the surface of the slit coating mold, thereby obtaining a slit coating mold with uniform liquid discharge.

[0084] Example 2

[0085] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The only difference between this embodiment and Example 1 is that the inorganic nano-silicon coating provided in Preparation Example 1 is replaced by the nano-titanium dioxide coating A provided in Preparation Example 2, and other conditions are the same as in Example 1.

[0086] Example 3

[0087] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The only difference between this embodiment and Example 1 is that the inorganic nano-silicon coating provided in Preparation Example 1 is replaced by the nano-titanium dioxide coating B provided in Preparation Example 3, and other conditions are the same as in Example 1.

[0088] Example 4

[0089] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge, the improvement method comprising the following steps: cleaning the lip surface and the surface of the receiving chamber of the slit coating blade in the slit coating die with polyether polyol 3300IN, and then spraying the hydrophilic polymer coating provided in Preparation Example 4 on the lip surface and the surface of the receiving chamber of the slit coating blade, with a spraying amount of 9g / m 2 , and dried at 100°C for 60 minutes to form a hydrophilic coating on the surface of the slit coating mold, thereby obtaining a slit coating mold with uniform liquid discharge.

[0090] Example 5

[0091] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The difference between this embodiment and embodiment 1 is that the method is dried at 60°C for 30 minutes and sintered at 200°C for 30 minutes. Other conditions are the same as those in embodiment 1.

[0092] Example 6

[0093] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The difference between this embodiment and embodiment 1 is that the method is dried at 60°C for 30 minutes and sintered at 400°C for 10 minutes. Other conditions are the same as those in embodiment 1.

[0094] Example 7

[0095] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The difference between this embodiment and embodiment 1 is that the spraying amount is adjusted to 15 g / m 2 , other conditions are the same as in Example 1.

[0096] Example 8

[0097] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The difference between this method and embodiment 1 is that the spraying amount is adjusted to 8 g / m 2 , other conditions are the same as in Example 1.

[0098] Example 9

[0099] This embodiment provides a method for improving the uniformity of liquid discharge from a slit coating die and a slit coating die with uniform liquid discharge. The difference between this embodiment and Embodiment 1 is that the spraying amount is adjusted to 6 g / m2, and other conditions are the same as those of Embodiment 1.

[0100] Comparative Example 1

[0101] This comparative example provides a slit coating die, which differs from Example 1 in that the steps of spraying inorganic nano-silicon coating, drying and high-temperature sintering are not performed, and other conditions are the same as those of Example 1.

[0102] Application Example 1

[0103] This application example provides a perovskite film, which is prepared by the following method:

[0104] (1) preparing a perovskite solution: adding N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:6 into a clean solution bottle, and then adding PbI2 and CH3NH3I to prepare a solution, wherein the concentrations of lead iodide (PbI2) and methylamine iodine (CH3NH3I) in the solution are both 1 mol / L, and then sealing the mouth of the solution bottle, placing it on a constant temperature heated stirrer at 50°C, and stirring for 2 h to obtain a perovskite solution;

[0105] (2) The perovskite solution prepared in step (1) is coated on a float glass by a slit coating process using the slit coating die with uniform liquid discharge provided in Example 1 to obtain a perovskite film.

[0106] Application Examples 2 to 9

[0107] Application Examples 2 to 9 respectively provide a perovskite film, which differs from Application Example 1 only in that the slit coating die with uniform liquid discharge provided in Examples 2 to 9 is used to replace the slit coating die with uniform liquid discharge provided in Example 1, and other conditions are the same as in Example 1.

[0108] Comparative application example 1

[0109] This comparative application example 1 provides a perovskite film, which differs from application example 1 only in that the slit coating die with uniform liquid discharge provided in comparative example 1 is used to replace the slit coating die with uniform liquid discharge provided in example 1, and other conditions are the same as those in example 1.

[0110] Performance Testing

[0111] Water contact angle: The water contact angles of the hydrophilic coatings prepared in Examples 1 to 9 and Comparative Example 1 were tested using a water contact angle tester, as shown in Table 1.

[0112] Film thickness non-uniformity: The film thickness non-uniformity test was performed on the perovskite film provided in Examples 1 to 9 and Comparative Application Example 1. A 30 cm × 40 cm perovskite film was divided into 16 equal parts, and the thickness of each part was tested to obtain the maximum thickness h1 and the minimum thickness h2, in nm, and the film thickness non-uniformity U = [(h1-h2) / (h1+h2)] × 100%. The test results are shown in Table 2.

[0113] Table 1

[0114] Example Water contact angle Example 1 4.8° Example 2 4.2° Example 3 4.5° Example 4 4.5° Example 5 4.9° Example 6 5.0° Example 7 4.2° Example 8 7.3° Example 9 10.7° Comparative Example 1 42.2°

[0115] Table 2

[0116]

[0117]

[0118] Depend on Figures 1 to 3 It can be seen that the wettability of the slot coating die surface can be effectively improved and the water contact angle can be reduced by forming a hydrophilic coating on the slot coating die surface.

[0119] It can be seen from the contents of Tables 1 and 2 that the water contact angle of the hydrophilic coating obtained by the method for improving the uniformity of liquid discharge from the slit coating die provided in Examples 1 to 8 is ≤10°, and the corresponding perovskite film provided in Application Examples 1 to 8 has a thickness unevenness U≤5%. The smaller the water contact angle, the lower the film thickness unevenness and the better the film thickness uniformity.

[0120] Compared with Examples 1, 7 and 8, the water contact angle decreases with the increase of spraying amount and the non-uniformity of film thickness becomes smaller.

[0121] Compared with Example 1, if the spraying amount is too low (Example 9), the water contact angle is larger, and the thickness non-uniformity of the corresponding perovskite film provided in Application Example 9 increases; it can be seen that the spraying amount of the method for improving the uniformity of liquid discharge from the slit coating die in the present invention is within a specific range, and the thickness uniformity of the prepared perovskite film is better.

[0122] Compared with Example 1, the water contact angle of the slit coating die not coated with the hydrophilic coating (Comparative Example 1) is large, and the thickness uniformity of the perovskite film prepared in the corresponding Comparative Application Example 1 is poor.

[0123] In summary, the present invention forms a hydrophilic coating on the surface of the slit coating die to prepare a slit coating die with uniform liquid discharge, which can improve the uniformity of slit coating liquid discharge and make the thickness of the prepared coating film uniform.

[0124] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for improving the uniformity of liquid discharge from a slit coating die, characterized in that: The improvement method comprises the following steps: coating a hydrophilic coating on the surface of the slit coating die to form a hydrophilic coating on the surface of the slit coating die to obtain a slit coating die with uniform liquid discharge; The surface of the slit coating die includes a lip surface of the slit coating blade and a surface of the accommodating chamber.

2. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 1, characterized in that: The slit coating die is a slit coating die cleaned with an organic solvent or a surfactant; Preferably, the organic solvent comprises any one of acetone, anhydrous ethanol or isopropanol, or a combination of at least two thereof; Preferably, the hydrophilic coating is a superhydrophilic coating; Preferably, the water contact angle of the super hydrophilic coating is ≤5°; Preferably, the hydrophilic coating comprises any one of an inorganic nano-silicon coating, a nano-titanium dioxide coating or a hydrophilic polymer coating; Preferably, the coating comprises spraying; Preferably, the spraying amount is 8 to 15 g / m 2 .

3. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 2, characterized in that: The hydrophilic coating comprises an inorganic nano-silicon coating or a nano-titanium dioxide coating, and the step of forming the hydrophilic coating on the surface of the slit coating mold specifically comprises the steps of drying and sintering; Preferably, the drying temperature is 60-100°C and the drying time is 10-30 minutes; Preferably, the sintering temperature is 120-400° C. and the sintering time is 10-30 min.

4. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 2 or 3, characterized in that: The preparation method of the inorganic nano-silicon coating comprises the following steps: (a) mixing hydrochloric acid and water to prepare a hydrochloric acid solution; (b) mixing tetraethyl orthosilicate and a solvent, adding the hydrochloric acid solution obtained in step (a), stirring, and standing to obtain a SiO2 sol; (c) mixing the SiO2 sol obtained in step (b) with a surfactant, stirring, and standing to obtain the inorganic nano-silicon coating.

5. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 4, characterized in that: The molar ratio of water to hydrochloric acid in step (a) is 1:(0.02-0.05); Preferably, the molar ratio of tetraethyl orthosilicate to solvent in step (b) is 1:(4-8); Preferably, the molar ratio of tetraethyl orthosilicate to hydrochloric acid is 1:(0.05-0.1); Preferably, the solvent in step (b) comprises ethanol; Preferably, the surfactant in step (c) comprises hexadecyltrimethylammonium bromide and / or sodium lauryl sulfate; Preferably, the mass of the surfactant in step (c) is 1% to 5% of the mass of the SiO2 sol; Preferably, the step (b) of adding the hydrochloric acid solution prepared in step (a) is dropwise adding the hydrochloric acid solution prepared in step (a); Preferably, the stirring temperature in step (b) is 20 to 60° C. and the stirring time is 1.5 to 2.5 h; Preferably, the standing time in step (b) is 15 to 20 hours; Preferably, the stirring temperature in step (c) is 20 to 40° C. and the stirring time is 1.5 to 2.5 h; Preferably, the standing time in step (c) is 8 to 24 hours.

6. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 2 or 3, characterized in that: The preparation method of the nano titanium dioxide coating comprises the following steps: (A) mixing butyl titanate, acetic acid and a solvent to obtain a light yellow solution; (B) Mixing the light yellow solution obtained in step (A) with a nitric acid solution to obtain a nano titanium dioxide coating.

7. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 6, characterized in that: The volume ratio of butyl titanate, acetic acid and solvent in step (A) is 10:(1-3):(25-35); Preferably, the mixing in step (A) is stirring mixing, and the stirring temperature is 20 to 40° C. and the time is 15 to 60 minutes; Preferably, the nitric acid solution in step (B) comprises nitric acid, ethanol and water; Preferably, the volume ratio of the nitric acid, ethanol and water is 0.5:(8-12):(0.5-1.5); Preferably, the volume ratio of the light yellow solution to the nitric acid solution in step (B) is 42:(5-15); Preferably, the mixing in step (B) is stirring mixing, and the stirring temperature is 20 to 40° C. and the time is 1 to 2 hours.

8. The method for improving the uniformity of liquid discharge from a slit coating die according to claim 2, characterized in that: The hydrophilic coating comprises a hydrophilic polymer coating; Preferably, the hydrophilic polymer coating comprises a hydrophilic polymer; Preferably, the hydrophilic polymer comprises a hydroxyl-containing hydrophilic polymer or a carboxyl-containing hydrophilic polymer; Preferably, the hydroxyl-containing hydrophilic polymer comprises any one or a combination of at least two of polyethylene glycol, polyvinyl alcohol or polyvinyl pyrrolidone; Preferably, the carboxyl-containing hydrophilic polymer comprises polyacrylic acid.

9. A slit coating die with uniform liquid discharge, characterized in that: The slit coating die with uniform liquid discharge is prepared by the method for improving the uniformity of liquid discharge from a slit coating die as described in any one of claims 1 to 8.

10. Use of the slit coating die with uniform liquid discharge as claimed in claim 9 in a coating process of perovskite.

Citation Information

Patent Citations

  • Slit coating unit, coating head and coating equipment

    CN105170406A